Struggle For Equality As Seen In Carol Ann Duffy’s Poem “Little Red Cap” - Paputungan, Vennalizha S.; Rorintulus, Olga; Andries, Fivy (Program Studi Pendidikan Bahasa Inggris, 2025)
The objective of this research is to elucidate the portrayal of the battle for equality in the poem